Synchronously improved thermal conductivity and mechanical property for polybenzimidazole composites by building the ternary hybrid nanofillers networks. Issue 5 (26th February 2022) - Mo, Rui; Zhu, Liuliu; Wu, Xinfeng; Guo, Wenyao; Min, Yulin; Fan, Jinchen
Abstract: A unique and highly efficient means to ameliorate the thermal conductivities (TCs) of polymers towards the polymer‐based thermal management materials is by introducing high‐thermal conductivity nanofillers to prepare polymer composites. However, in order to obtain high TC, the large content of a single filler often brings serious dispersibility problems which greatly affect the improvement of the TC. Meantime, in a polymeric matrix, it is difficult for a single nanofiller itself to form the heat conduction path. Herein, in order to overcome the above‐mentioned problems, we introduced highly thermal conductive nanofillers like two‐dimensional (2D) functionalized boron nitride nanoflakes (f‐BNNS), MXene (Ti3 C2 Tx ), and one‐dimensional (1D) silver nanowires (AgNWs) into the polybenzimidazole (PBI) matrix together. It is found that the introduction of high‐aspect‐ratio AgNWs could not only improve the dispersion of nanofillers under high‐loading amounts but also facilitate the formation of heat conduction path with thermally conductive f‐BNNS and Ti3 C2 Tx . When the total loading amount of MXene, f‐BNNS, and AgNWs was 50.5 wt% (MXene: 25 wt%, f‐BNNS: 25 wt%, AgNWs: 0.5 wt%), the yield and ultimate tensile strengths of the f‐BNNS/MXene/AgNWs/PBI‐50/0.5 composite film reached ~204.8 and ~ 203.6 MPa, respectively. Meantime, the in‐plane and through‐plane TCs of f‐BNNS/MXene/AgNWs/PBI‐50/0.5 composite film also could reach ~31.97 and ~ 2.25 W·m −1  K −1 with increases of ~52.2% and ~ 80% in comparison with those of f‐BNNS/MXene/PBI composites, respectively, having the same contents of f‐BNNS and MXene. Abstract :